12. To be, Or Not to be (Informed)? An Unthinkable Choice - Grigoraș Florin (Sciendo, 2022)
The reported research refers to the implications of Information Theory, Information and Communication Technologies and Applied Ontologies, in the educational process, in general, with specific attention to artistic education. We emphasize the major role of the informational methods for knowledge organisation, calling on such concepts as shared use and interoperability of information, in the context of the recent teaching and learning paradigms shift. Three contributions with significant potential are introduced: an extension of the navigationist paradigm and two formal methods, aiming at improved information processing for teaching and learning in the arts, with a new perspective on the definition of the work of art.